HUBUNGAN SUPERVISI KEPALA SEKOLAH DAN KINERJA GURU TERHADAP MUTU LULUSAN DI SEKOLAH DASAR NEGERI DALAM WILAYAH KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU KALIMANTAN SELATAN - Agus Syarifuddin (STKIP Paris Barantai, 2014)
In these areas, the problems in the field of education is not only the low quality of education, but there is the tendency for the quality divide between the provinces, districts and even between villages and towns. This is partly caused by the diversity of potential human resources, natural resources, culture and others are less supportive of the educational process and output. In addition, management practices that are centralized and bureaucratic participate inhibit creativity of the managers of education in the area so that the quality of graduates will always be left behind.Test the validity of items with product moment correlation technique, the analysis of load factor with the criteria on the size of load factor (factor loading) and payload together (communality). Charge factor of 0.70 (50% variance) special, 0.63 (40% variance) is very good, 0.55 (30% variance) either, 0.45 (20% variance) enough, and 0.32 (10% variance) was (Andrew, 1973). These items can be accepted is that the magnitude of the charge factor of 0.32. Test reliability coefficient Alpha of Cronback item with standard criteria for reliability coefficient greater than 0.70.Â Keyword: Supervisi Kepala Sekolah, Kinerja Guru, Mutu Lulusan